Fecundidade e pareamento educacional no Brasil : um estudo de Coorte - Monteiro da Silva, José Henrique Costa, 1993- (2019)
Orientadores: Everton Emanuel Campos de Lima, Maria Coleta Ferreira Albino de Oliveira